Tratamiento de las eventraciones del Hemiabdomen inferior Mediante Plastia Preperitoneal de refuerzo con mallas Sintéticas - Maglione, Hugo; Armand Ugon, Alfredo; Garat, Eduardo; Mayol, Ricardo (Cirugía del Uruguay, 1983)
Useful spaces far reinforcement sintetic grafts placement in reparation of eventrations are described. Advantages of preperitoneal space is remarked. Technic is summarized and experience in 15 patients and 0 % of recurrency is presented.